2020
DOI: 10.1080/09654313.2020.1726294
|View full text |Cite
|
Sign up to set email alerts
|

Public houses and house prices in Great Britain: a panel analysis

Abstract: This paper examines the relationship between public houses or 'pubs' and house prices in Great Britain. Using a unique dataset, comprising statistical indicators for 373 local authorities registered between 2005 and 2015, the authors investigate this relationship from a panel data perspective. The analysis identifies a strong positive association between an increase in the number of pubs and house prices, showing different patterns with regard to pubs located in urban, suburban and rural areas. Results offer a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 38 publications
1
9
0
Order By: Relevance
“…The real estate prices of Wuhan are increasing at an alarming rate, associated with rapid industrialization and urbanization and consequent demands for various categories of real estate. A spatial heterogeneity analysis of real estate prices is considered crucial for revealing major issues in real estate market development, understanding effective strategies of economic macro control, and promoting the high-quality development of internal economics [46][47][48][49]. This paper uses the listed residential sale prices of Wuhan City, Hubei Province, China as characteristic price data, constructs a characteristic price model [30,[50][51][52][53][54], and conducts an experimental analysis.…”
Section: Study Area and Datamentioning
confidence: 99%
“…The real estate prices of Wuhan are increasing at an alarming rate, associated with rapid industrialization and urbanization and consequent demands for various categories of real estate. A spatial heterogeneity analysis of real estate prices is considered crucial for revealing major issues in real estate market development, understanding effective strategies of economic macro control, and promoting the high-quality development of internal economics [46][47][48][49]. This paper uses the listed residential sale prices of Wuhan City, Hubei Province, China as characteristic price data, constructs a characteristic price model [30,[50][51][52][53][54], and conducts an experimental analysis.…”
Section: Study Area and Datamentioning
confidence: 99%
“…The expansion of craft breweries has increased the variety of different craft beers available to British consumers, who now have a wide range of flavours from which to choose (Cabras, 2020). Several studies in literature analyse the demand for beer and its price elasticity in relation to brand and type (Tegene,1990; Lee and Tremblay, 1992; Hausman et al , 1994; Freeman, 2001), although there is still a paucity of research addressing cross-price elasticity among different types of beer.…”
Section: Literature Reviewmentioning
confidence: 99%
“…In the the UK, several studies have focused on public houses or pubs and their importance in terms of economic development, social aggregation and the communities’ well-being (Maye et al , 2005; Muir, 2009; Cabras and Mount, 2017; Cabras and Lau, 2019). Many of these studies illustrated the positive impact generated by pubs in terms of employment opportunities, community cohesion and social engagement, reporting a progressing decline in their number and highlighting the potential negative implications for local communities and economies (Cabras et al , 2020).…”
Section: Introductionmentioning
confidence: 99%
“…It has been confirmed that the Coronavirus Disease 2019 (COVID- 19) pandemic has posed significant impacts on the global economy [4], which has led to varying degrees of stagnation or even recession in the development of the global economy [5][6][7][8]. As the real estate market is one of the most active markets in China and plays a vital role in the Chinese economy, exploring the spatial heterogeneity of housing prices is Land 2023, 12, 167 2 of 24 considered to be crucial for revealing major issues in real estate market development, understanding effective strategies of economic macro-control, and promoting the highquality development of internal economics in the post-COVID-19 pandemic era [9][10][11][12].…”
Section: Introductionmentioning
confidence: 99%